2017
DOI: 10.1038/modpathol.2016.222
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 and Rb1 in esophageal small-cell carcinoma: their possible involvement in pathogenesis

Abstract: Clinicopathological features and pathogenesis of esophageal small-cell carcinoma remain unclear. We hypothesized common cellular origin and pathogenesis in small-cell carcinoma of esophagus and lung associated with SOX2 overexpression and loss of Rb1. Expression of squamous-basal markers (CK5/6 and p40), glandular markers (CK18 and CEA), SOX2, and Rb1 were evaluated in 15 esophageal small-cell carcinomas, 46 poorly differentiated squamous cell carcinomas, and 88 small-cell lung carcinoma, as well as 16 embryon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…In 181 (74%) cases, the original pathology diagnosis provided from the contributing institutions was available. The same cohort was either partly or fully included in 2 previously published studies [20, 21], one that dealt with small-cell carcinoma of the esophagus in comparison to SCLC, and the other with PD-L1 expression and survival in lung NENs. Clinical and follow-up data were available in 227 (93%) and 226 patients (93%), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 181 (74%) cases, the original pathology diagnosis provided from the contributing institutions was available. The same cohort was either partly or fully included in 2 previously published studies [20, 21], one that dealt with small-cell carcinoma of the esophagus in comparison to SCLC, and the other with PD-L1 expression and survival in lung NENs. Clinical and follow-up data were available in 227 (93%) and 226 patients (93%), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The mitotic count was evaluated in 2 mm 2 in the area showing the highest density of mitosis. Immunohistochemistry for synaptophysin, chromogranin A, CD56, TTF1, napsin A, CK5/6, p63, p40, and Ki67 was performed using previously described methods [20]. Synaptophysin, chromogranin A, and CD56 were assessed in a semiquantitative manner using a previously established scoring system (immunoreactive score, 0–12) [23].…”
Section: Methodsmentioning
confidence: 99%
“…A previous study demonstrated that abnormal expression of MAPK1 contributes to the occurrence of ESCA [35]. It has been reported that RB1 expression was downregulated in esophageal small-cell carcinoma [36]. CLTC is associated with endocytosis and mitosis in cancer cells [37].…”
Section: Discussionmentioning
confidence: 94%
“…However, the literature on the prevalence of CK18 expression is controversial for many cancers . For example, CK18 positivity has been described in 30% to 100% of oral squamous cell carcinomas (40,47), 0-100% of non-small cell lung cancers (44,46), and 0-43% of esophageal squamous cell carcinomas (18,45). These con icting data are likely to be caused by the use of different antibodies, immunostaining protocols, and criteria to determine CK18 positivity in these studies.…”
Section: Introductionmentioning
confidence: 94%